Characterization of Pediococcus acidilactici postbiotic and impact of postbiotic-fortified chitosan coating on the microbial and chemical quality of chicken breast fillets - Incili, Gokhan Kursad; Karatepe, Pinar; Akgol, Muzeyyen; Kaya, Busra; Kanmaz, Hilal; Hayaloglu, Ali Adnan (Elsevier, 2021)
This study was carried out to characterize antioxidant activity, total phenolic content, and the phenolic and flavonoids profile of postbiotic of Pediococcus acidilactici and to evaluate the effects of postbiotics (10% and 50%) alone and in combination with chitosan coating (1%) on the microbial and chemical quality of chicken breast fillets during storage at 4 degrees C. Antioxidant activity and total phenolic content of the postbiotics were found to be 1291.02 +/- 1.5 mg/L TEAC and 2336.11 +/- 2.36 mg/L GAE, respectively. The most abundant phenolic was vanillic acid, followed by t-caffeic, gallic, and caftaric acids. The postbiotic-chitosan (50% + 1%) combination decreased L. monocytogenes and S. Typhimurium counts by 1.5 and 2.1 log(10) CFU/g, respectively, compared to the control (P < 0.05). This combination decreased the total viable count (TVC), lactic acid bacteria (LAB), and psychrotrophic bacteria count compared to the control (P < 0.05). No differences were found in thiobarbituric acid (TBA) values among the samples during storage (P > 0.05). Postbiotic treatment did not significantly change the pH values and color properties of the breast fillets (P > 0.05). Postbiotic-chitosan combinations extended the shelf-life by up to 12 days compared to the control. In conclusion, the postbiotic-chitosan combination can be used to preserve and improve the microbial quality of chicken meat products.
Keywords: Postbiotics; Cell-free supernatant; Characterization; Chicken breast fillet; Antimicrobial activity; Chemical quality